2020
DOI: 10.3390/antiox9121198
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Attenuation of Paraoxonase 1 Activity Induces Proatherogenic Changes in Plasma Proteomes of Mice and Humans

Abstract: High-density lipoprotein (HDL), in addition to promoting reverse cholesterol transport, possesses anti-inflammatory, antioxidative, and antithrombotic activities. Paraoxonase 1 (PON1), carried on HDL in the blood, can contribute to these antiatherogenic activities. The PON1-Q192R polymorphism involves a change from glutamine (Q variant) to arginine (R variant) at position 192 of the PON1 protein and affects its enzymatic activity. The molecular basis of PON1 association with cardiovascular and neurological dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Both findings suggest a proatherogenic proteomic shift by reducing PON1 levels. The PON1-192QQ genotype was associated with downregulation of F13B and SERPINA1, both involved in the coagulation process, thus increasing the risk of atherothrombosis (Sikora et al, 2020). Serum PON1 concentrations in the general population show very high variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both findings suggest a proatherogenic proteomic shift by reducing PON1 levels. The PON1-192QQ genotype was associated with downregulation of F13B and SERPINA1, both involved in the coagulation process, thus increasing the risk of atherothrombosis (Sikora et al, 2020). Serum PON1 concentrations in the general population show very high variability.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most studied PON1 nucleotide change is the rs622 (c.575A > G) missense mutation, which leads to a glutamine -arginine replacement at position 192 (p.Gln192Arg). This mutation leads to increased paraoxonase activity (Sikora et al, 2020). rs854560 (c.163A > T) is a missense mutation that results in the replacement of leucine with methionine at position 55 (p.Leu55Met).…”
Section: Introductionmentioning
confidence: 99%
“…PON1 also promotes the differentiation of macrophages into an anti-inflammatory phenotype [146]. An interesting study [147] demonstrated that genetically reduced PON1 concentration induces proatherogenic changes in plasma proteomes in humans and mice. The study investigated the influence of the least efficient isoforms of PON1 genetic polymorphisms in humans and Pon1−/− genotype in mice and found that both genetic modifications induce changes in the plasma proteome that affect biological networks involving proteins participating in lipoprotein metabolism, in CVD in neurological diseases, in immune response, inflammatory response, in cell-to-cell signaling, and immune-cell trafficking.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…PON1 also promotes the differentiation of macrophages into an anti-inflammatory phenotype [146]. A recent study of note [147] showed that genetically reduced PON1 concentration induces proatherogenic changes in plasma proteomes in humans and mice. The study investigated the influence of the least efficient isoforms of PON1 genetic polymorphisms in humans and Pon1−/− genotype in mice and found that both genetic modifications induce changes in the plasma proteome that affect biological networks involving proteins participating in lipoprotein metabolism, in CVD in neurological diseases, in immune response, inflammatory response, in cell-to-cell signaling and immune-cell trafficking.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%